Dampak Kepemimpinan Wu Zetian Pada Masyarakat Tiongkok Tradisional Dalam Novel The True Story Of China’s Cleopatra Karangan Jonathan Clements - Artika Gunawan Abdullah; Tri Budianingsih; Sri Hartati (Universitas Al Azhar Indonesia, 2023)
The Tang Dynasty is one of the most famous dynasties in China. In addition to the discovery of many discoveries, this dynasty also has many interesting stories. One of them is the story of Empress Wu Zetian (武则天Wǔzétiān). who is the only female emperor in China. The story of Empress Wu Zetian, the female emperor, has attracted a lot of interest from the public and even novelists. This study reviews the impact of Empress Wu Zetian's leadership on traditional Chinese society in the novel The True Story of China's Cleopatra. The author uses a qualitative descriptive approach, a research approach by examining qualitative sources to examine the impact of Empress Wu Zetian's leadership on traditional Chinese society in the novel The True Story of China's Cleopatra. From the research that has been done, it is known that during her reign, Empress Wu Zetian has made many positive impacts on current traditional Chinese society. Examples such as the existence of a state examination system that can be followed by all circles of society, the abolition of taxes to workers and farmers, the development of Buddhism and also equal rights for women in its time.Keywords - The True Story of China’s Cleopatra, Empress Wu Zetian, Tang Dynasty, The Impact of her rule